OFFICE LETTERS: TYPES, EFFECTIVE PRINCIPLES, AND HISTORY IN THE TIME OF THE PROPHET - Selly Wulandari; Ananda Faradina; Nasrun Harahap (International Journal of Multidisciplinary Reseach, 2025)
Correspondence is an essential component of office administration systems, serving as a medium for both formal and informal written communication. In the professional world, letters function not only as a means of conveying information but also as legal documents and institutional records. This study aims to examine the various types of office correspondence, the principles of effectiveness in letter writing, and to explore the history of correspondence during the time of the Prophet Muhammad (peace be upon him). The research method employed is a qualitative approach with a literature review as the primary source of data. The findings indicate that understanding the types of letters and applying effective principles such as structure, clarity, and linguistic efficiency are crucial in supporting administrative performance. Furthermore, correspondence practices during the Prophet’s era demonstrate that letters were used as strategic tools for diplomacy and da’wah. This study is expected to contribute to enhancing the understanding and professional practice of office correspondence grounded in historical values.